Classroom behavioral problems and the methods used to solve them in the first cycle schools in Lattakia governorate from the teachers' point of view (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The aim of this research is to identify the classroom behavioral problems and the methods used to solve them in the first cycle schools in Lattakia Governorate from the teachers’ point of view and the impact of the variables (training courses, school location, number of years of experience, and educational and educational qualifications) in that.The research reached the following results:• The degree of classroom discipline problems facing teachers in the first cycle schools of the basic education stage was high. - The degree of educational problems facing teachers in the schools of the first cycle of the basic education stage was medium. The most used methods in solving classroom behavioral problems from the point of view of teachers in the schools of the first cycle of the basic education stage is to clarify classroom rules and procedures since the beginning of the school year, and to provide a suitable classroom environment for learners.• There are statistically significant differences with regard to classroom behavioral problems and the methods used to address them from the basic education stage in Lattakia governorate according to the variable of training courses in the field of classroom management, and according to the school location variable, and according to the academic qualification variable, and there were no statistically significant differences according to the variable of the number of years of experience in teaching.